Organizing pneumonia co‐existing with carcinoid tumour: complete resolution with bronchoscopic tumour resection. Issue 4 (7th March 2019) - Bajaj, Divyansh; Todd, Nevins; Hossain, Rydhwana; Mahajan, Karan; Burrows, Whitney; Sachdeva, Ashutosh
Abstract : Organizing pneumonia is a well‐known clinical entity resulting in response to noxious stimuli causing lung injury. It is known to occur with infectious disease processes, neoplasms, post lung surgery or radiation therapy and when idiopathic, is called cryptogenic organizing pneumonia. We present an unusual case of a 48‐year‐old woman who presented with chronic cough and progressive dyspnoea while being on macrolide therapy for Lyme disease. Computerized tomography of chest demonstrated a well‐circumscribed nodule in the lingula and bilateral central ground glass opacities. Transbronchial biopsies were consistent with carcinoid tumour in the lingula and organizing pneumonia in bilateral lung fields. Bronchoscopic relief of obstruction was performed by mechanical debulking of the tumour, with subsequent complete resolution of bilateral opacities, consistent with resolution of organizing pneumonia without the need for steroid therapy. Abstract : We report an unusual case of organizing pneumonia occurring as a consequence of obstruction due to a carcinoid tumour and its complete resolution by bronchoscopic relief of obstruction without the need for steroid therapy.